Analisis Perhitungan dan Pelaporan PPN untuk Menentukan Pajak Terutang di CV Greens Production - Handayani, Hani; Kurniawan, Aceng (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
CV Greens Production is a company that has been confirmed as a taxable entrepreneur and is required to comply with tax regulations. This study discusses how to calculate and report value added tax at CV Greens Production. The purpose of this study is to find out how to calculate and report value added tax in accordance with applicable laws, as well as to find out the amount of VAT payable. The research method used is qualitative by way of observation, interviews, and documentation by carrying out calculations according to the company and comparing based on the tax law through tax invoice data and reporting in the 2022 period. Based on the results of the research conducted, it can be concluded that CV Greens Production has not implemented related to input VAT crediting, the calculation and reporting are in accordance with Law No. 42 of 2009 and result in VAT payable of IDR 25,708,210. Keywords: VAT, Calculation, Reporting, VAT Payable.